Les causes de la mortalité pendant la Grande Famine - Philippe Brillet (Revue Française de Civilisation Britannique)
A comparison with the Nordeste region of Brazil suggests that the Irish, despite their poverty and recurring food shortages, were in good health prior to the Great Famine. But the exceptional length of the Famine weakened their immunitary defenses and they became vulnerable to numerous infections. Yet medical knowledge at the time was not only insufficient to correctly identify the causes of death, it actually increased mortality, notably by grouping people in fever hospitals where contagion was rife.